Community Empowerment Through Utilization of Information Technology to Improve Management of Health Introspection at An-Nur Student Islamic Boarding School - Dwi Handayani; Mursyidul Ibad; Endang Sulistiyani; Akmalina Ziadati Sukmaningtyas; Odilia Ika Auliya; Maulidatul Hasanah; Nur Muhammad Ali Al-Faizi; Rifky Dwi Aditya Iryawan (Community Development Journal, 2022)
Islamic boarding schools are places that are very vulnerable to disease transmission. The number of Islamic boarding schools that are adaptive to the progress of the times can change the behavior of their people towards a better life, namely by using technology. An-Nur Islamic Boarding School is a modern Islamic boarding school that does not yet have an up to date recording and reporting system that is integrated with the primary health care for monitoring health risks. The purpose of this community service is to empower student administrators in utilizing web-based information technology for monitoring health risks in Islamic boarding schools. The implementation method used is a Participatory Technology Development and educative approach. The output targets to be achieved are increasing knowledge about monitoring health risks in Islamic boarding schools, skills in measuring nutritional status and skills in utilizing health risk information technology. The results showed an increase in the average score of students' knowledge about the importance of surveillance-based health risk monitoring. Before being given education, the average score of knowledge of students was only 69. And after being given education, the average score of knowledge increased to 91. In addition, 80% of participants were able to measure nutritional status with the correct stages. And skills in using information technology in recording health risk factors are also very good. Participants is very easy and fast in using health information technology. The use of information technology in monitoring health risks is expected to help improve introspective health management in Islamic boarding schools. There needs to be more widespread socialization to other Islamic boarding schools and ongoing assistance related to the use of web-based information technology in monitoring health risks in Islamic boarding schools